Oral anticoagulants and concurrent rifampin administration in tuberculosis patients with non-valvular atrial fibrillation - Hwang, Ki Won; Choi, Jin Hee; Lee, Soo Yong; Lee, Sang Hyun; Chon, Min Ku; Lee, Jungkuk; Kim, Hasung; Kim, Yong-Giun; Choi, Hyung Oh; Kim, Jeong Su; Park, Yong-Hyun; Kim, June Hong; et al. (BMC cardiovascular disorders, 2023)
Background Evidence and guidelines for Non-vitamin K antagonist oral anticoagulants (NOACs) use when prescribing concurrent rifampin for tuberculosis treatment in patients with non-valvular atrial fibrillation (NVAF) are limited. Methods Using the Korean National Health Insurance Service database from January 2009 to December 2018, we performed a population-based retrospective cohort study to assess the net adverse clinical events (NACE), a composite of ischemic stroke or systemic embolism and major bleeding, of NOACs compared with warfarin among NVAF patients taking concurrent rifampin administration for tuberculosis treatment. After a propensity matching score (PSM) analysis, Cox proportional hazards regression was performed in matched cohorts to investigate the clinical outcomes. Results Of the 735 consecutive patients selected, 465 (63.3%) received warfarin and 270 (36.7%) received NOACs. Among 254 pairs of patients after PSM, the crude incidence rate of NACE was 25.6 in NOAC group and 32.8 per 100 person-years in warfarin group. There was no significant difference between NOAC and warfarin use in NACE (hazard ratio [HR], 0.74; 95% confidence interval [CI], 0.48–1.14; P = 0.172). Major bleeding was the main driver of NACE, and NOAC use was associated with a statistically significantly lower risk of major bleeding than that with warfarin use (HR, 0.63; 95% CI, 0.40–1.00; P = 0.0499). Conclusions In our population-based study, there was no statically significant difference in the occurrence of NACE between NOAC and warfarin use. NOAC use may be associated with a lower risk of major bleeding than that with warfarin use.